Determination of intramedullary nail based on centerline adaptive registration - Liu, Xiaolong; Li, Jin; Luan, Kuan (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Internal fixation with intramedullary nail is the gold standard for treatment of femoral shaft fractures. However, both the mismatch between intramedullary nail and medullary cavity and the inaccurate positioning of entry point will lead to the deformation of intramedullary nail after implantation. The study aimed to determine a suitable intramedullary nail with optimal entry point for a specific patient based on centerline adaptive registration. Method: A homotopy thinning algorithm is employed to extract the centerlines of femoral medullary cavity and intramedullary nail. The two centerlines are registered to obtain a transformation. The medullary cavity and intramedullary nail are registered based on the transformation. Next, plane projection method is employed to calculate the surface points of intramedullary nail laid outside the medullary cavity. According to the distribution of outside points, an iterative adaptive registration strategy is designed to decide an optimal position of the intramedullary nail in medullary cavity. The isthmus centerline is extended to the femur surface, where the entry point of the intramedullary nail is located. The suitability of all intramedullary nails is calculated and the most suitable one is determined. Results: The growth experiment indicated that the registration is affected by the position and length of isthmus centerline. Geometrical experiment showed that this method could find the best registration position of intramedullary nail and select the optimal intramedullary nail for a specific patient. In the model experiments, the determined intramedullary nail could be successfully placed into the medullary cavity through the optimal entry point. An intramedullary nail was available when its suitability for a specific patient was less than 0.133. In addition, the distal hole was accurately located within 14.28 seconds. Conclusion: These results suggest that the proposed method can select a suitable intramedullary nail with optimal entry point. The position of intramedullary nails can be determined in the medullary cavity, while deformation being avoided. The determined intramedullary nail can provide the maximum support strength with as little damage to the intramedullary tissue as possible. The proposed method provides preparation aid for internal fixation with intramedullary nail guided by navigation systems or extracorporeal aimers.